Integrating Artificial Intelligence in Speaking Skill Development: Teachers’ Perceptions at an Indonesian Islamic University - Miftahul Mufid; Muassomah Muassomah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The application of artificial intelligence (AI) in language learning is rapidly increasing, while research on the use of AI in teaching the Arabic language in Indonesia remains limited. As an exploratory study , this research aims to explore the perceptions of lecturers regarding the application of artificial intelligence (AI) in teaching speaking skills in Arabic and its impact on learning effectiveness at Nahdlatul Ulama University of Sunan Giri (UNUGIRI). Using a qualitative methodology with a phenomenological design, this study includes in-depth interviews with two Arabic language lecturers and classroom observations. The results indicate that lecturers have positive perceptions regarding the potential of AI to enhance speaking practice and provide instant feedback to students. However, they also identified challenges such as curriculum adaptation and the need for continuous professional development. The impacts of using AI on learning include increased student motivation, more practice opportunities, and personalized learning. The main challenges are in authentic assessment and the integration of cultural context. it is among the first to investigate the implementation of AI in Arabic language instruction within the Indonesian higher education context; it adopts a phenomenological approach to capture in-depth insights into lecturers’ lived experiences; and it offers a comparative analysis of two AI tools Google Assistant and FunEasyLearn in supporting Arabic speaking skills. In conclusion, the application of AI in learning Arabic at UNUGIRI shows promising potential, but it requires a balanced approach between technological innovation and traditional teaching methods. This study highlights the importance of continuous development in integrating AI into Arabic language curricula in higher education in Indonesia.